2008
DOI: 10.1017/s0004972708000348
|View full text |Cite
|
Sign up to set email alerts
|

Vector Subspaces of the Set of Non-Norm-Attaining Functionals

Abstract: An example is found of a nonreflexive Banach space X such that the union of {0} and the set X * \ NA(X ) of non-norm-attaining functionals on X contains no two-dimensional subspace.2000 Mathematics subject classification: 46B20, 46B03, 46B07.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…When is N A(X) spaceable? These questions have been deeply studied in [35] by Bandyopadhyay and Godefroy, who provided, among other results, conditions that ensure that N A(X) is not spaceable; see also the recent works [1,153] for more results on the linear structure of N A(X). Very recently, García-Pacheco and Puglisi [158] showed that every Banach space admitting an infinite dimensional separable quotient can be equivalently renormed in such a way that the set of its norm attaining functionals contains an infinite dimensional linear subspace.…”
Section: Some Remarks and Conclusion General Techniquesmentioning
confidence: 99%
“…When is N A(X) spaceable? These questions have been deeply studied in [35] by Bandyopadhyay and Godefroy, who provided, among other results, conditions that ensure that N A(X) is not spaceable; see also the recent works [1,153] for more results on the linear structure of N A(X). Very recently, García-Pacheco and Puglisi [158] showed that every Banach space admitting an infinite dimensional separable quotient can be equivalently renormed in such a way that the set of its norm attaining functionals contains an infinite dimensional linear subspace.…”
Section: Some Remarks and Conclusion General Techniquesmentioning
confidence: 99%